How Many of the Biopsy Decisions Taken at Inexperienced Breast Radiology Units Were Correct? - (:unkn) unknown (AVES, 2017)
Objective: In this study, we aimed to determine the need for biopsy in patients referred from other clinics for the performance of biopsy with the suspicion of breast cancer. Materials and Methods: 112 patients were included in the study. It was decided that their biopsies be performed following examinations in other clinics and they presented to the breast radiology unit of our hospital for a second opinion. The demographic characteristics, diagnostic studies completed in the other centers, properties of lesions, decision made as a result of examinations and BI-RADS (Breast Imaging Reporting and Data Systems) categorizations were recorded on the registration forms of the study patients. In addition, the quality of examinations, reasons of repeat tests, additional tests features and the last decision of our clinic were documented. The obtained data were analyzed in terms of re-examination, additional tests and change in the biopsy decision. Changes in the biopsy decisions for patients were specifically inquired. Results: The biopsy decisions were cancelled in our breast radiology unit for 63 out of 112 patients (56.3%) whose biopsy decisions were made at an external institute. For 42 patients, examinations made by the other clinics were deemed adequate, yet there was no need for biopsy in 22 of them. The biopsy decisions were cancelled for 27 out of 47 patients (57.4%) with repeat examination and 18 out of 28 patients (64.3%) with additional tests because of the insufficient test quality. Conclusion: Incorrect, inadequate breast screening and false positivity were higher at inexperienced institutes.
Keywords: Breast Radiology; biopsy; experience; SCREENING MAMMOGRAPHY; CANCER; IMPACT; WOMEN; MULTICENTER; RISK; REQUIREMENTS; MORTALITY; DISTRESS; QUALITY